Effect of shear rate on the performance of membrane-assited lead acid battery - Hafiz, W. A. (2004)
The effect of shear rate during membrane fabrication on the performance of membrane-assisted lead acid battery has been investigated. The application of lead acid battery normally faces the problem of water decomposition. This phenomenon is due to the factor of charge-discharge reaction in the battery and heat accumulation caused by hot tropical climate and heat generated from engine compartment. Gas separation membranes were prepared through dry-wet phase inversion method using various polysulfone concentrations and different shear rates. Each of these membranes was applied on the battery vent holes for the purpose of retaining electrolyte from evaporating to the atmosphere. The most suitable membrane, which retains the most electrolyte will be chosen to be applied on the soon-to-be developed membrane-assisted maintenance free battery. This maintenance free battery will not need any topping up of deionized water due to electrolyte losses. Gases emitted from both conventional and membrane-assisted lead acid batteries were analyzed with Near Infrared Fourier Transform Raman Spectrometer in order to differentiate the compositions of hydrogen and oxygen gases.